Silver-Prompted Carbonitration of Acrylamides for the Synthesis of Nitrating Oxindoles - Wei, Xiao-Hong; Wu, Quan-Xiang; Yang, Shang-Dong (Synlett, 2015)
A silver-prompted carbonitration of alkenes involving concomitant direct C–H functionalization and C–N bond formation to synthesize nitrating oxindoles has been developed. The CR TH2 receptor antagonist skeleton can be obtained from one of the products with further modification.
Keywords: silver; N-methyl-N-arylacrylamide; carbonitration; nitrating oxindoles